Farm buildings - Balmer, Frank Everett (My University, 1905)
Introduction: Building is one of the great events that comes far apart, and it is a very important undertaking in that the result is to be the farmer's home. Unfortunately, too little forethought and planning is given to the undertaking and often the result is far from satisfactory. After mistakes are once made in a structure they cannot be readily or cheaply corrected. Seldom does the farmer conduct any great building movement at one time. Often his abilities will not permit or his aim is not clear so that he must begin, or prefers to begin modestly and add to what he has as there is demand for enlargement. This plan is preferable, for if extensive building is done at one time there will likely be a greater tendency to he too be expensive, but may not serve Hence, it is desirable that subsequent enlargement, for creased and the enlargement the elaborate and the result may not only for the constant need of the farmer. Hence, it is desirable that the planning should be so as to facilitate money can be saved and convenience of the home may be made so as to be in keeping with the steady growth of the farmer's enterprise and his surroundings. And, too, a steady growth permits that the structures may be more substantially put up, so they will be more permanent. Americans will probably never erect great castles and palaces that stand for centuries, as have many of the English, yet they are coming to realize, as have many of the European people, the necessity of suitable and substantial buildings for the country homes. Already, the eastern section of our country has made great progress in the erection of spacious and permanent buildings. True, that portion of our country is older, has more wealth, yet since the central and western parts of our country are so universally engaged in agriculture al pursuits, there is great necessity that they should amply provide to conserve what they have produced, as well as furnish themselves with all the conveniences and comforts that may come to the country life.
Citation: Balmer, Frank Everett. Farm buildings. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Elments of Choosing Location; Foundation; Cellar and Value; Theses